IMPLEMENTASI KEBIJAKAN JALUR ZONASI PADA PENERIMAAN PESERTA DIDIK BARU PADA JENJANG SMA Se-KECAMATAN SOMBA OPU KABUPATEN GOWA: 217-224 - Khaeril Aswat; Imam Suyitno; Muh. Sudirman (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
This study aims to find out (1) how to implement the zoning route, (2) the impact that occurs in the application of the zoning route, (3) efforts to overcome the negative impacts of the zoning route on PPDB for SMA levels in Somba Opu District, Gowa Regency. Qualitative research and using a descriptive approach. The data sources used are primary data and secondary data. Data collection techniques include: Observation, Interview and Documentation. The data obtained from the research results were processed using descriptive qualitative data analysis. The results of this study indicate that (1) The implementation of the zoning pathway for the Admission of New Students at the Senior High School level in Somba Opu District, Gowa Regency has been adequate in its application because there were no deviations from the applicable provisions for Admission of New Students. (2) The impact of the implementation of the pathway on the Admission of New High School Students in Somba Opu District, Gowa Regency has 2 impacts, namely positive and negative in its application, where the negative impacts found are less than the positive impacts found, the negative impacts found are 3 impacts negative and 6 positive impacts. (3) Efforts to overcome the negative impact of the zoning route on the Admission of New High School Students throughout the Somba Opu District, Gowa Regency, namely 1) the need for changes in the selection process in the form of changing the selection method for determining distances using mileage instead of straight dance, 2) needs to be done addition of school infrastructure, 3) schools must be maximal in conducting socialization and parents should also be required to seek news or information related to PPDB, especially this zoning route.